Pengaruh Akupresure Titik SP6 terhadap Intensitas Nyeri Dismenore Primer pada Remaja Putri di Banjarmasin Timur Tahun 2025 - Nugraine, Aan; Rusmilawaty; Dewi, Vonny Khresna; Prihatanti, Nur Rohmah (Bunda Edu-Midwifery Journal (BEMJ), 2026)
Introduction: Primary dysmenorrhoea is a common complaint among adolescent girls and can interfere with daily activities and academic performance. Non- pharmacological interventions such as acupressure are increasingly used as safe and practical alternatives. Acupressure at the SP6 (Sanyinjiao) point is believed to reduce menstrual pain by improving pelvic blood circulation and stimulating endorphin release. Methods: This study employed a quantitative approach using a quasi-experimental design with a one-group pre and post intervention. The study was conducted among 30 adolescent girls experiencing primary dysmenorrhoea in East Banjarmasin in 2025. Pain intensity was measured before and after the SP6 acupressure intervention using the Numerical Rating Scale (NRS) ranging from 0 to 10. Data were analysed using univariate analysis and the Wilcoxon Signed Rank Test. Results: The Wilcoxon test showed a significant reduction in pain intensity (p < 0.001), indicating a significant effect of SP6 acupressure on primary dysmenorrhoea pain. Conclusion: SP6 acupressure effectively reduces primary dysmenorrhoea pain in adolescent girls. This simple and safe non-pharmacological method can be practised independently and recommended as an alternative menstrual pain management strategy.